Learning from First Nations - Brown, David D. (Canadian Institute of Planners, 1999)
My presentation at this year's CIP Conference looked at how planners, and planning schools in particular, can extend their work in First Nation regions in order to support social development and equity. This follow-up article outlines the social conditions and opportunities for planning in Aboriginal communities, and offers some thoughts on the need for greater Aboriginal involvement in the planning process. Ma conférence au congrès de l'lnstitut canadien des urbanistes en 1999 portait sur Jes possibilités offertes aux urbanistes (et en particulier aux écoles d'urbanisme) en mission dans les regions des Premières Nations de favoriser le développement de la société et la justice sociale. Cet article fait suite à cette conférence et situe les conditions et les perspectives sociales des communautés autochtones dans le contexte de l'urbanisme. Il avance quelques idées quant à la nécessité d'une participation accrue des autochtones euxmêmes dans l'aménagement de leurs communautés. Abstract in English and French; text in English. https://viurrspace.ca/bitstream/handle/10613/6174/Brown.pdf?sequence=3